Comorbidities reduce survival and quality of life in COPD with severe lung hyperinflation - Else A.M.D. ter Haar; Dirk-Jan Slebos; Karin Klooster; Simon D. Pouwels; Jorine E. Hartman (ERJ Open Research)
Rationale and aim Patients with COPD often present with a significant number of comorbidities, which are thought to be related to a higher mortality risk. Our aim was to investigate the prevalence and impact of comorbidities on survival and quality of life (QoL), specifically in patients with emphysema characterised by severe lung hyperinflation. Patients and methods Data were prospectively collected from patients who visited our hospital for evaluating their eligibility for a bronchoscopic lung volume reduction treatment and were included in the Groningen Severe COPD cohort (NCT04023409). Comorbidities were patient-reported by a questionnaire and were validated with patients’ medical records. QoL was assessed with the St Georges Respiratory Questionnaire. Results We included 830 COPD patients with Global Initiative for Chronic Obstructive Lung Disease (GOLD) stage III and IV. The total number of comorbidities was an independent predictor of survival when adjusting for other factors influencing survival (HR 1.12, 95% CI 1.05–1.20, p<0.001). Of the individual comorbidities, pulmonary arterial hypertension (HR 1.53, 95% CI 1.01–2.32, p=0.045), low body mass index (HR 1.63, 95% CI 1.16–2.27, p=0.004) and anxiety (HR 1.46, 95% CI 1.11–1.92, p=0.007) were independently associated with worse survival. Moreover, patients having 3, 4 or >5 comorbidities had a significantly (all p<0.05) worse QoL, in comparison to patients without comorbidities. Conclusion Our results show that comorbidities were associated with lower survival and poor QoL in emphysema patients characterised by severe hyperinflation. Appropriate treatment of treatable traits, including anxiety, low body mass index and pulmonary arterial hypertension, could lead to a survival benefit and improvement in QoL in this specific patient population.